Effects of Genotypes and Mulching on Growth and Yield of Onion - Ghimire, Susmita; Subedi, Raj; Pandey, Gobinda (Agriculture Development Journal, 2024)
Selection of the right genotype and optimizing management practices are essential for higher crop productivity. In the area of onion cultivation, the correlation between onion genotypes and mulching remains a relatively unexplored terrain. To identify this association, an experiment was conducted at the Horticulture Development Resource Centre, Kaski, from November to April 2023. Structured in two factorial randomized complete block designs, the experiment featured five genotypes—AVON 1052, AVON 1103, Khumal 1, Khumal 2, and Red Creole (check variety)—and two mulching levels, namely black plastic mulch and control, with four replications. Significant variations were found among genotypes in response to mulching. Red Creole, Khumal 1, and AVON 1103 exhibited a significant difference in plant height and leaf number. AVON 1052, Khumal 2, and Khumal 1 showed a substantial divergence in average total bulb diameter with and without mulching. Furthermore, with the exception of Red Creole, other genotypes demonstrated a significant difference in total bulb yield, favoring mulching with black plastic. Khumal 2, produced a yield of 11.7 t ha-1 without mulching, attributed its success to larger bulb diameter, more leaves (8), and taller plants (66.8 cm), while Khumal 2 (16 t ha-1) under mulching showed similar yielding potential as Red Creole. Ultimately, the recommendation of mulching in Khumal 2 was given owing to the bulb-splitting problem in Red Creole and indifferent yield in Khumal 2 as compared to Red Creole. This research shows how better onion types and using mulch can enhance onion production and promote agricultural sustainability in Nepal.